A combined retrospective, prospective and experimental study of Ornithobacterium rhinotracheale infection in chickens. Issue 5 (3rd September 2019) - Gornatti-Churria, Carlos Daniel; Loukopoulos, Panayiotis; Prescott, Matthew; Petruccelli, Miguel A.; Machuca, Mariana A.
ABSTRACT: The aim of this study was to examine the histopathological and immunohistochemical changes caused by natural and experimentally-induced Ornithobacterium rhinotracheale infection in the respiratory system of chickens. To this end, three different studies were carried out. The first was a retrospective study of 82 field cases with respiratory disorders compatible with O. rhinotracheale infection. The bacterium was immunohistochemically detected in the lungs in 48 of 82 field cases, and 50 β-haemolytic (BH) and non-haemolytic (NH) strains were isolated. In the second study, an experimental model of the disease was created using 3-week-old broiler chickens, to identify possible differences of pathogenicity between the BH and NH isolates by the intravenous (IV) and intratracheal (IT) inoculation routes (IR). The group challenged with the NH isolate showed more severe lung lesions than the group challenged with the BH isolate at 7-days postinoculation (p.i.). The 14-day p.i. groups challenged with either the BH or NH isolates by the IT or IV IR had a higher histologic grade of pulmonary and hepatic lesions and a higher total histologic grade of lesions suggesting more severe pathology with longer time of exposure. A direct association between the inoculation routes and the organs affected was shown. Finally, a slaughterhouse study was carried out from October 2014 to May 2015, in which the histologic grade of lesions was significantly higher in immunohistochemically positive for O. rhinotracheale lungs of dead-on-arrival chickens.